Stereotactic Radiosurgery for Atypical (World Health Organization II) and Anaplastic (World Health Organization III) Meningiomas: Results From a Multicenter, International Cohort Study. Issue 5 (19th May 2021) - Shepard, Matthew J; Xu, Zhiyuan; Kearns, Kathryn; Li, Chelsea; Chatrath, Ajay; Sheehan, Kimball; Sheehan, Darrah; Faramand, Andrew; Niranjan, Ajay; Kano, Hideyuki; Gurewitz, Jason; Bernstein, Kenneth; et al.
Abstract: BACKGROUND: Atypical and anaplastic meningiomas have reduced progression-free/overall survival (PFS/OS) compared to benign meningiomas. Stereotactic radiosurgery (SRS) for atypical meningiomas (AMs) and anaplastic meningiomas (malignant meningiomas, MMs) has not been adequately described. OBJECTIVE: To define clinical/radiographic outcomes for patients undergoing SRS for AM/MMs. METHODS: An international, multicenter, retrospective cohort study was performed to define clinical/imaging outcomes for patients receiving SRS for AM/MMs. Tumor progression was assessed with response assessment in neuro-oncology (RANO) criteria. Factors associated with PFS/OS were assessed using Kaplan-Meier analysis and a Cox proportional hazards model. RESULTS: A total of 271 patients received SRS for AMs (n = 233, 85.9%) or MMs (n = 38, 14.0%). Single-fraction SRS was most commonly employed (n = 264, 97.4%) with a mean target dose of 14.8 Gy. SRS was used as adjuvant treatment (n = 85, 31.4%), salvage therapy (n = 182, 67.2%), or primary therapy (1.5%). The 5-yr PFS/OS rate was 33.6% and 77.0%, respectively. Increasing age (hazard ratio (HR) = 1.01, P  < .05) and a Ki-67 index > 15% (HR = 1.66, P  < .03) negatively correlated with PFS. MMs (HR = 3.21, P  < .05), increased age (HR = 1.04, P  = .04), and reduced KPS (HR = 0.95, P  = .04) were associated with shortened OS. Adjuvant versus salvage SRS did not impact PFS/OS. A shortened interval between surgery and SRS improved PFS for AMs (HR = 0.99, P  = .02) on subgroup analysis. Radiation necrosis occurred in 34 (12.5%) patients. Five-year rates of repeat surgery/radiation were 33.8% and 60.4%, respectively. CONCLUSION: AM/MMs remain challenging tumors to treat. Elevated proliferative indices are associated with tumor recurrence, while MMs have worse survival. SRS can control AM/MMs in the short term, but the 5-yr PFS rates are low, underscoring the need for improved treatment options for these patients. Graphical Abstract: